Criminal and Administrative Legal Characteristics of Offenses in The Field of Countering Drug Trafficking: Insights from Ukraine - Volobuieva, Olena; Leheza, Yevhen; Pervii, Vita; Plokhuta, Yevhenii; Pichko, Roman (Yustisia, 2023)
Drug addiction in Ukraine has been showing signs of an epidemic and represents one of the potential threats to Ukraine's national security. This article highlights the regulation of the ratio of criminal and administrative liability as to countering offences in the sphere of trafficking of narcotic drugs, psychotropic substances, their analogues and precursors. The research method is presented as comparative-legal (legislation of Ukraine, Holland, Germany, Italy, Spain, Switzerland, Netherlands, Austria, Portugal and Finland) and systematic analysis. The sanctions for drug crimes provided for in the legislation, countries are divided into three groups, namely hard policy group, strict control group, and liberal group. Summing up the analysis of the legal regulation of the fight against drug crime in different countries, it should be noted that international legal acts govern most countries' legislation. At the same time, the legislation and executive system of punishments of various states in combating drug crimes are specific, due not so much to the country's national characteristics but to the concretely formed criminogenic situation in this area.